How to (dis)solve Nagel's paradox about moral luck and responsibility - Fernando Rudy Hiller (Manuscrito)
Abstract In this paper I defend a solution to the moral luck problem based on what I call "a fair opportunity account of control." I focus on Thomas Nagel's claim that moral luck reveals a paradox, and argue that the apparent paradox emerges only because he assumes that attributions of responsibility require agents to have total control over their actions. I argue that a more modest understanding of what it takes for someone to be a responsible agent-i.e., being capable of doing the right thing for the right reasons-dissolves the paradox and shows that responsibility and luck aren't at odds.